2019
DOI: 10.3389/fphar.2019.01153
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in the Treatment of Infections Caused by Multidrug-Resistant Organisms

Abstract: Nanotechnology using nanoscale materials is increasingly being utilized for clinical applications, especially as a new paradigm for infectious diseases. Infections caused by multidrug-resistant organisms (MDROs) are emerging as causes of morbidity and mortality worldwide. Antibiotic options for infections caused by MDROs are often limited. These clinical challenges highlight the critical demand for alternative and effective antimicrobial strategies. Nanoparticles (NPs) can penetrate the cell membrane of pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
225
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(265 citation statements)
references
References 77 publications
1
225
0
Order By: Relevance
“…In this section, the basic characteristics of each type of synthesis are briefly described. In chemical synthesis, the Turkevich method and Brust-Schiffrin synthesis are mainly used [43]. The Turkevich method is based on the reduction of the boiling solution of silver salt with a solution of citrate salt.…”
Section: Synthesis Of Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, the basic characteristics of each type of synthesis are briefly described. In chemical synthesis, the Turkevich method and Brust-Schiffrin synthesis are mainly used [43]. The Turkevich method is based on the reduction of the boiling solution of silver salt with a solution of citrate salt.…”
Section: Synthesis Of Agnpsmentioning
confidence: 99%
“…One problematic aspect of AgNPs wound dressings is that there are reported cases of bacterial resistance to AgNPs. For example, resistance to AgNPs attributed to sil genes has been reported in clinical isolates of Klebsiella pneumoniae and Enterobacter cloacae from burn cases [43]. Thus, the continuous development of a new combination of nanomaterials, antibiotics, polymers, methods of incorporation and types of reduction of silver to obtain various shapes of NPs is essentially necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are some limitations to the use of these nanomaterials before their successful translation to clinics. One is the limited amount of data on the use of such systems to tackle infection in in vivo models, thus preventing adequate assessment of optimal dose, appropriate administration routes and possible interaction of nanoparticles with cells and tissues, whose toxicological profile is not completely understood ( Baptista et al, 2018 ; Lee et al, 2019 ).…”
Section: Alternative Antibacterial Therapiesmentioning
confidence: 99%
“…For NPs combined with antibiotics, the antimicrobial effects were found to be increased considerably. [ 206 ] Gandhi and Khan reported enhanced antimicrobial activity of AgNPs in the presence of bacitracin against E. coli and S. paratyphi (control 0 mm, test 22 and 18 mm inhibition zone, respectively), ampicillin against Corynebacterium diphtheria (control 0 mm, test 14 mm), kanamycin against K. pneumoniae (control 19 mm, test 30 mm), for gentamycin against P. aeruginosa (control 18 mm, test 34 mm), and bacitracin, gentamycin, erythromycin, and ciprofloxacin against S. aureus (control 0, 14, 19, and 21 mm, test 12, 29, 32, and 30 mm, respectively). [ 38 ] Singh et al found an antimicrobial activity of biosynthesized AgNPs against B. anthracis , B. cereus , E. coli , C. albicans, V. parahaemolyticus , and S. enterica .…”
Section: Antimicrobial Efficacy Of Nanoparticlesmentioning
confidence: 99%